2022
DOI: 10.21203/rs.3.rs-2195635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Power of the Fintech to Control Pollution: the Case of the Mobile Money in Somalia

Abstract: Financial technology is a crucial component for developing the financial sector, which has an undulating effect on the economy's well-being. The financial institutions enable the economic agents to invest in the real sector to boost productivity and drive economic growth. This paper examines the causal link between mobile money and carbon emission in Somalia to discover if mobile money can be used to control pollution and tackle environmental deterioration. This study uses quarterly data spanning from 2012 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Extending the literature to environmental pollution and Fintech, we notice that most studies have shown that Fintech can reduce environmental pollution and promote sustainable development [ 25 , 26 , 27 ]. In terms of greenhouse gases, some researchers have found that the development of Fintech can significantly reduce carbon dioxide emissions [ 28 , 29 , 30 ]. However, to date, little is known about the green attributes of Fintech [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extending the literature to environmental pollution and Fintech, we notice that most studies have shown that Fintech can reduce environmental pollution and promote sustainable development [ 25 , 26 , 27 ]. In terms of greenhouse gases, some researchers have found that the development of Fintech can significantly reduce carbon dioxide emissions [ 28 , 29 , 30 ]. However, to date, little is known about the green attributes of Fintech [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facilitated by mobile banking and other similar financial apps, most financial activities (e.g., making a deposit, taking out a loan, and making investments) take place on mobile devices especially through smartphones (Frost, 2020). By March 2020, 776.08 million people adopt mobile transactions in China (Daxue Consulting, 2021) so that the value of apps in emerging markets is expected to exceed $870 billion in 2026 (Maynard, 2022).…”
Section: Introductionmentioning
confidence: 99%